Shexiang Baoxin Pill, Derived From the Traditional Chinese Medicine, Provides Protective Roles Against Cardiovascular Diseases - Lu, Li; Sun, Xiaodong; Chen, Chen; Qin, Yating; Guo, Xiaomei (Frontiers in Pharmacology, 2018)
Shexiang Baoxin Pill (SBP), belonging to the traditional Chinese medicine, has been broadly applied to the treatment of cardiovascular diseases including coronary heart disease, heart failure and hypertension in the East Asia for decades. Emerging pharmacological studies reveal that SBP displays pleiotropic roles in protecting the cardiovascular system, as seen by the promotion of angiogenesis, amelioration of inflammation, improvement of endothelium dysfunction, mitigation of dyslipidemia, repression of vascular smooth muscle cell proliferation and migration and restraint of cardiac remodeling. In term of clinical practice, the clinical trials and meta-analysis have proved the efficacy and safety of SBP. In this review, we, for the first time, systemic summarize the cardioprotective effects and underlying mechanisms of SBP and provide novel insights into its future research directions from the experimental and clinical perspectives.